2D imidazole- and thiazole- based COFs. Syntheses parameters using linker exchange. - Linder, Markus (My University, 2025)
Constructing new materials for proton conduction above 100 °C is vital for the development of robust proton-exchange membrane fuel cells. Utilizing the remarkable proton conducting properties of polybenzimidazole and the tunable properties of covalent organic frameworks (COF), it is possible to create chemically stable structures that can be used as scaffolds for dopants. This thesis aimed to shed light on both how to increase the crystallinity of imidazole and thiazole COFs, and how to construct a reversible, highly crystalline imine-based COF that can be used as a prenetwork (PN) for the irreversible COF synthesis. The PN underwent linker exchange in order to create imidazole COFs with crystallinity equal to that of the PN. Different configurations of temperature, modulator, oxidant, excess reagent, and time were tested to examine their impact on the PN and imidazole COFs. The results indicate the successful creation of crystalline imidazole COFs when synthesized with modulators, pressured air and excess reagent during linker exchange. Modulators were shown to have low impact on the crystallinity of the PN and a high impact on the crystallinity of the imidazole COF, making their use vital during imidazole COF synthesis.
Keywords: COF; imidazole; thiazole; pre-network; linker exchange; modulator